Radiation-induced formation of acrylated palm oil nanoparticle using pluronic F-127 microemulsion system - Tajau, Rida; Wan Yunus, Wan Md Zin; Mohd Dahlan, Khairul Zaman; Mahmood, Mohd Hilmi; Hashim, Kamaruddin; Ismail, Maznah; Salleh, Mek Zah; Che Ismail, Rosley (Universiti Putra Malaysia Press, 2013)
This study demonstrated the utilization of radiation-induced initiator methods for the formation of nanoparticles of Acrylated Palm Oil (APO) using aqueous Pluronic F-127 (PF-127) microemulsion system. This microemulsion system was subjected to gamma irradiation to form the crosslinked APO nanoparticles. Dynamic light scattering (DLS), Fourier Transform Infrared (FTIR) spectroscopy and Transmission Electron Microscopy (TEM) were used to characterize the size and the chemical structure of the nanoparticles. As a result, the size of the APO nanoparticle was decreased when the irradiation dose increased. The decrease in size might be due to the effects of intermolecular crosslinking and intramolecular crosslinking reactions of the APO nanoparticles during irradiation process. The size of the nanoparticle is in the range of 98 to 200 nanometer (nm) after irradiation using gamma irradiator. This radiation-induced method provides a free initiator induced and easy to control process as compared to the classical or chemical initiator process. The study has shown that radiation-induced initiator methods, namely, polymerization and crosslinking in the microemulsion, were promising for the synthesis of nanoparticles.